International human rights treaty to change social patterns: the convention on the elimination of all forms of discrimination against women - Cho, Seo-Young (Georg-August-Universität Göttingen, 2010)
"This paper analyzes empirically whether the ratification of the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), advocating the multiple dimensions of women’s rights, affects the level of women’s rights in a country. Measuring commitments to the CEDAW based on reservations by member states, I test whether the Convention enhances women’s rights; in particular, (i) whether the effects are stronger if a member country has a higher level of democracy; and (ii) whether the effects are most pronounced in the dimension of women’s social rights, a special focus of the Convention. Using panel data for 126 countries during 1981-2007, I do not find statistically significant effects of the CEDAW alone on any dimension of women’s rights. However, I do find a positive impact of the CEDAW on women’s social rights if combined with a higher degree of democracy. These findings are robust to the choice of control variables and the method of estimation. In particular, taking into account the potential reverse-causality does not alter the main conclusions."